Ionic Mechanisms Underlying the Excitatory Effect of Orexin on Rat Subthalamic Nucleus Neurons - Li, Guang-Ying; Zhuang, Qian-Xing; Zhang, Xiao-Yang; Wang, Jian-Jun; Zhu, Jing-Ning (Frontiers in Cellular Neuroscience, 2019)
Central orexinergic system deficiency results in cataplexy, a motor deficit characterized with a sudden loss of muscle tone, highlighting a direct modulatory role of orexin in motor control. However, the neural mechanisms underlying the regulation of orexin on motor function are still largely unknown. The subthalamic nucleus (STN), the only excitatory structure of the basal ganglia, holds a key position in the basal ganglia circuitry and motor control. Previous study has revealed a wide distribution of orexinergic fibers as well as orexin receptors in the basal ganglia including the STN. Therefore, in the present study, by using whole-cell patch clamp recording and immunostaining techniques, the direct effect of orexin on the STN neurons in brain slices, especially the underlying receptor and ionic mechanisms, were investigated. Our results show that orexin-A elicits an excitatory effect on STN neurons in rats. TTX does not block the orexin-induced excitation on STN neurons, suggesting a direct postsynaptic action of the neuropeptide. The orexin-A-induced inward current on STN neurons is mediated by the activation of both OX1 and OX2 receptors. Immunofluorescence result shows that OX1 and OX2 receptors are co-expressed and co-localized in STN neurons. Furthermore, Na+-Ca2+ exchangers and inward rectifier K+ channels co-mediate the excitatory effect of orexin-A on STN neurons. These results demonstrate a dual receptor in conjunction with the downstream ionic mechanisms underlying the excitatory action of orexin on STN neurons, suggesting a potential modulation of the central orexinergic system on basal ganglia circuitry as well as its related motor control and motor diseases.